2012
DOI: 10.1016/j.joca.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Gd-DTPA2− into articular cartilage

Abstract: The results revealed that passive diffusion of Gd-DTPA²⁻ was significantly slower than previously assumed, leading to overestimation of the GAG content at equilibrating times of few hours. Moreover, Gd-DTPA²⁻ distribution was found to depend not only on GAG content, but also on collagen content and diffusion direction. Interestingly, the dGEMRIC technique was found to be most sensitive to cartilage degradation in the early stages of diffusion process, suggesting that full equilibrium between gadopentetate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 35 publications
(47 reference statements)
3
36
0
Order By: Relevance
“…Despite the weak correlation, this finding suggests that, in addition to sGAG content, the integrity of cartilage extracellular matrix also has an influence on contrast material influx into cartilage. Therefore, dGEMRIC outcomes appear not to be dependent on sGAG content alone, which was recently also suggested by others (34,35). The difference between the strength in correlation between the outcomes of dGEMRIC and cartilage sGAG and collagen content, however, suggests that sGAG is the composite that has the most influence on contrast material distribution throughout the articular cartilage.…”
Section: Musculoskeletal Imaging: Assessment Of Sulphated Glycosaminosupporting
confidence: 62%
“…Despite the weak correlation, this finding suggests that, in addition to sGAG content, the integrity of cartilage extracellular matrix also has an influence on contrast material influx into cartilage. Therefore, dGEMRIC outcomes appear not to be dependent on sGAG content alone, which was recently also suggested by others (34,35). The difference between the strength in correlation between the outcomes of dGEMRIC and cartilage sGAG and collagen content, however, suggests that sGAG is the composite that has the most influence on contrast material distribution throughout the articular cartilage.…”
Section: Musculoskeletal Imaging: Assessment Of Sulphated Glycosaminosupporting
confidence: 62%
“…As with previous studies, which found that the diffusion coefficient that controls diffusion rate based on Fick's law [267], decreased with depth, and it correlated positively with the fluid content and negatively with solid content, in particular, proteoglycan content [14,15,[268][269][270][271].…”
Section: Discussionsupporting
confidence: 88%
“…It has been showed experimentally that the diffusion of solutes increased with articular degeneration [15,270,277]. The diffusive transport also became faster after enzymatically degraded articular cartilage, which only digests proteoglycan [270,278,279].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations